2017
DOI: 10.4172/2329-6798.1000236
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Selected Organic Compounds Influence on Water Quality Along the Olifants River in South Africa

Abstract: Water is a crucial natural resource, indispensable to food production, life, the environment, power generation, industry, sanitation and hygiene. Organochlorine Pesticides (OCPs) in the environment are not wanted due to their negative effects on human beings and animals. As a result, there is a need to continuously monitor their presence in the environment. In this study, surface water samples were collected once a month during the dry season and during wet season from selected five points along the Olifants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The linearity of calibration data was assessed by applying the regression analysis model in the Analysis Toolpak of Excel. The resulting least square estimates were used to calculate the limits of detection and quantification (LOD and LOQ) (Miller and Miller, 2010;Shrivastava and Gupta, 2011). Data were further subjected to analysis of variance (ANOVA), descriptive statistics, correlation plots and multivariate methods.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The linearity of calibration data was assessed by applying the regression analysis model in the Analysis Toolpak of Excel. The resulting least square estimates were used to calculate the limits of detection and quantification (LOD and LOQ) (Miller and Miller, 2010;Shrivastava and Gupta, 2011). Data were further subjected to analysis of variance (ANOVA), descriptive statistics, correlation plots and multivariate methods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the seasonal changes were also expected, since these correlate with increases and/or decreases in water levels, variations in climatic conditions, which may be exacerbated by run-off, as well as differences in anthropogenic activities (Montory et al, 2017;Baqar et al, 2018;Wang et al, 2018). Moja et al (2017) found that the site closest to Loskop Dam, namely Waterval, demonstrated seasonal variability in pesticide levels. Similar temporal and spatial observations have also been made in other water bodies (Montory et al, 2017;Baqar et al, 2018;Wang et al, 2018).…”
Section: Distribution Of Ocps In Water and Sedimentmentioning
confidence: 93%
See 3 more Smart Citations